Skateboarding’s Olympic journey: do the performance profiles of top athletes remain consistent? - Fouillot, Chloé; Saulière, Guillaume; Antero, Juliana; Sedeaud, Adrien; Toussaint, Jean-François (Frontiers in Physiology, 2025)
IntroductionSince its inclusion in the Tokyo 2020 Olympics, skateboarding has highlighted diverse age profiles among elite athletes. This study aims to characterize the relationship between age and performance in Street Skateboarding and examine how it has evolved with the sport’s growing professionalization.MethodsThe dataset includes 2,822 performances by 498 women and 12,116 by 2,784 men from international street skateboarding competitions (2001–2024). Athlete number and gender ratios were compared between 2017 and 2024 vs 2001–2016 periods in order to assess the evolution of the competitive context, with analysis of new and returning athletes. Performance was quantified using a dynamic rank-order logit model (ROL). Moore’s exponential model and IMAP tracked the age-performance relationship, with adjusted R-squared for model fit. Peak performance ages, estimated performances, and AUC were analyzed for trends.ResultsSince 2016, the number of international competitors has doubled for men (x2.13) and quadrupled for women (x4.02), narrowing the male-to-female participating ratio from 10.56 to 5.59. Records for new competitors have been consistently surpassed, particularly for women. Both Moore and IMAP models strongly explain the age-performance relationship (R2: 0.84–0.94). According to Moore and IMAP models, peak performance ages are estimated at respectively 18.12 and 16.25 for women and 22.51 et 21.34 for men. For women, age of peak performance significantly evolved toward younger ages over time, with a sharper drop from 2021 to 2024. For men, both AUC and age at peak performance increased significantly, indicating a widening of the optimum performance age range.DiscussionThe inclusion of skateboarding into the Olympic programs has expanded career opportunities, lowering peak performance age for women and broadening the optimal age range for men. This study is intended to help skateboarding stakeholders estimate athletes’ potential for future Olympiads and adapt development strategies. The age at peak performance trajectory for female athletes warrants special attention.